Statistical optimization and kinetic studies on removal of Zn2+ using functionalized carbon nanotubes and magnetic biochar - Mujawar, Mubarak; Alicia, R.; Abdullah, E.; Sahu, J.; Haslija, A.; Tan, J. (Elsevuer BV, 2013)
A comparative study on the adsorption capacity of functionalized carbon nanotubes (CNTs) and magnetic biochar for the removal of Zn 2+ was investigated. Statistical analysis revealed that the optimum conditions for the highest removal of Zn 2+ are at pH 10, dosage 0.09 g, agitation speed and time of 120 rpm and 120 min respectively. The removal efficiency of Zn 2+ for an initial concentration of 1.1 mg/L using functionalized CNT was 99% and using magnetic biochar was 75%. The maximum adsorption capacities of 1.05 and 1.18 mg/g for functionalized CNT and magnetic biochar respectively. The adsorption isotherms are well described by both Langmuir and Freundlich models and adsorption kinetic obeyed pseudo-second order.